2007
DOI: 10.3989/scimar.2007.71n4811
|View full text |Cite
|
Sign up to set email alerts
|

Effects of recreational fishing on three fish species from the <i>Posidonia oceanica</i> meadows off Minorca (Balearic archipelago, western Mediterranean)

Abstract: SUMMARY: Experimental fishing and visual censuses were conducted at nine Posidonia oceanica sites off Minorca exposed to different levels of fishing intensity to assess the effects of recreational fishing on the species that dominate the catch. Total catch per unit effort (CPUE) was highly seasonal and a statistically significant interaction term existed between the season and the level of fishing intensity. CPUE decreased everywhere at the end of the fishing season (autumn), but such a reduction was more inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 13 publications
0
16
1
Order By: Relevance
“…In the Balearic Islands (NW Mediterranean), S. scriba is one of the most frequently targeted species for recreational boat anglers (Morales-Nin et al 2005). Recent studies have used S. scriba to assess the impacts of recreational fisheries (Cardona et al 2007, Alós 2008. Thus, information on movements of S. scriba is relevant for the management of recreational fisheries.…”
Section: Introductionmentioning
confidence: 99%
“…In the Balearic Islands (NW Mediterranean), S. scriba is one of the most frequently targeted species for recreational boat anglers (Morales-Nin et al 2005). Recent studies have used S. scriba to assess the impacts of recreational fisheries (Cardona et al 2007, Alós 2008. Thus, information on movements of S. scriba is relevant for the management of recreational fisheries.…”
Section: Introductionmentioning
confidence: 99%
“…1). The 3 MPAs differ in how long they have been protectedMedes Islands in Catalunya has been protected since 1983, Cabrera National Park in Mallorca since 1991 and north of Menorca since 1999 -but fish recovery has been observed in all MPAs (Garcia-Rubies & Zabala 1990, García-Charton et al 2004, Cardona et al 2007, although none are likely to have reached full recovery (Guidetti & Sala 2007). Within each region, 3 sites were sampled at 3 depths (5, 15 and 30 m) on algal-dominated rocky habitats in the summer, when fish abundance and activity tend to be highest (Sala & Zabala 1996, Tomas et al 2005, Prado et al 2007).…”
Section: Study Sitesmentioning
confidence: 99%
“…The few studies carried out in the Mediterranean region revealed that recreational fishing catches appear to be far from negligible (MORALES-NIN et al, 2005;CARDONA et al, 2007), but these studies also suggest that the economic impact of RF is considerable, and in some regions greater than that of professional fishing (FRANQUESA et al, 2004). Moreover, signs of competition between recreational and professional fishing reveal the need for comprehensive management in Mediterranean coastal areas (LLORET et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%